Ocenjevanje natančnosti deblovnic in volumenskih funkcij - Hladnik, David (Zbornik gozdarstva in lesarstva, 2012)
Comparisons of stem volume estimation techniques were performed based on equations of Huber, Smalian and Newton, and a cubic spline interpolation of points along the silver fir tree stems. Results indicate that Newton`s and Huber`s equations were the most accurate in determining volumes of old silver fir trees (age up to 200 years and average dbh 59 cm). The obtained tree volumes were the basis for the standing timber estimation in the forest inventory. Despite their rather simple structure, the Slovene Čokl (1959) tariff functions proved to be sufficiently accurate (average residual in percentage of the mean volume < 1%, R2=0.87). The proportion of the individualtree volume variance explained increased by 5 % for standard two-entry volume tables and by 11% for three-parameter volume functions.
Keywords: Abies alba Mill.; jelka; tarife; volumen debeljadi; volumenske funkcije